A review of musculoskeletal ultrasound training guidelines and recommendations for sport and exercise medicine physicians. (August 2013) - Boyce, SH; Murray, AD; Jeffrey, M
Sport and exercise medicine (SEM) physicians are increasingly using musculoskeletal ultrasound (MSK US) in their clinical practice, but are they competent to do so? No formal training accreditation programme exists and courses are of variable length and quality. Training standards for other specialties practising MSK US are reviewed in the UK, Europe and Worldwide. Recommendations are given for training standards for UK SEM physicians.